Análise da implantação do Sistema de Informação de Atenção à Saúde Indígena na Bahia - Valverde, Larissa de Faro (2018)
This study aims to measure the degree of implantation (DI) of the Indigenous Healthcare Information System (IHIS) in the Special Indigenous Sanitary District of Bahia (ISSD-BA). An evaluative study, specifically an analysis of implementation was conducted in ISSD-BA, with a quantitative approach, and elaboration of a Logical Model (LM) and Matrix of Analysis and Judgment (MAJ) to establish the criteria, parameters and scores in order to define the DI. The MAJ was validated by means of Agreement Rate (AR) and Content Validity Index (CVI) by a panel of experts in the thematic area of Health of Indigenous Peoples. The overall AR obtained was 95% and the CVI was 0.8. After validation, MAJ covered 33 criteria. Data to obtain the DI were descendant from a questionnaire derived from the MAJ and applied to the workers of the decentralized units of the District (Base Poles), system typists and local managers, and to the professionals of the ISSD-BA, linked to the Division Healthcare for Indigenous Peoples (DHIP). There was a low level of implementation of IHIS at ISSD-BA (41%), with greater weaknesses in relation to material and logistical resources, personnel resources and management, use and dissemination of information. It is necessary to recover the function of the information system as a potential tool for decision-making, investing in activities of permanent education to the workers, so that they are provided with the necessary resources to develop actions that imply in improving the Indigenous People’s Healthcare.